Effects of isolated or combined carbohydrate and caffeine supplementation between 2 daily training sessions on soccer performance - Andrade-Souza, V. A.; Bertuzzi, R.; Gomes de Araujo, G.; Bishop, D.; Lima-Silva, A. E. (Applied Physiology, Nutrition, and Metabolism, 2015)
This study aimed to investigate whether isolated or combined carbohydrate (CHO) and caffeine (CAF) supplementation have beneficial effects on performance during soccer-related tests performed after a previous training session. Eleven male, amateur soccer players completed 4 trials in a randomized, double-blind, and crossover design. In the morning, participants performed the Loughborough Intermittent Shuttle Test (LIST). Then, participants ingested (i) 1.2 g/kg body mass/h CHO in a 20% CHO solution immediately after and 1, 2, and 3 h after the LIST; (ii) CAF (6 mg/kg body mass) 3 h after the LIST; (iii) CHO combined with CAF (CHO+CAF); and (iv) placebo. All drinks were taste-matched and flavourless. After this 4-h recovery, participants performed a countermovement jump (CMJ) test, a Loughborough Soccer Passing Test (LSPT), and a repeated-sprint test. There were no main effects of supplementation for CMJ, LSPT total time, or best sprint and total sprint time from the repeated-sprint test (p > 0.05). There were also no main effects of supplementation for heart rate, plasma lactate concentration, rating of perceived exertion (RPE), pleasure-displeasure, and perceived activation (p > 0.05). However, there were significant time effects (p < 0.05), with heart rate, plasma lactate concentration, RPE, and perceived activation increasing with time, and pleasure-displeasure decreasing with time. In conclusion, isolated and/or combined CHO and CAF supplementation is not able to improve soccer-related performance tests when performed after a previous training session.